Evaluating Shade Selection Procedure for Anterior Teeth among Dental House Surgeons and Dental Practitioners of Karachi - Samejo, Imran; Kumar, Bharat; Lone, Muneeb Ahmed; Musharraf, Hira; Memon, Lubna; Lone, Maham Muneeb (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To evaluate the shade selection procedure for anterior teeth among dental house surgeons, general dentists and specialists of Karachi. Methodology: This descriptive cross-sectional study was carried out to assess knowledge, attitude and practice regarding shade selection among house surgeons, general dentists and specialistsof Karachi from February-April 2020. A structured questionnaire consisting of demographic data along with multiple choice questions related to shade matching was used to collect data. Questionnaires were distributed by hand and electronically through google forms by non-probability convenience sampling to participants who fulfilled the inclusion criteria. House surgeons, general dentists and specialists involved in provision of fixed restorations were included in the study. Participants who refused to give written informed consent were excluded from the study. SPSS v.18.0 was used for data analysis. Results: Out of the 350 forms distributed, 290 forms were returned completely filled, giving a response rate of 82.9%. Majority of house surgeons (70.96%), general dentists (72.46%) and specialists (56.75%) used visual method for shade selection in their practice, using the Vita classic shade guide. About 60% of specialist always selected the shade before any procedure and involved their team members and patients’ opinion, in comparison 59% of house surgeon always selected shade after completion of procedure. Most of house surgeon never filled shade mapping chart and faced difficulty during shade selection. Majority of practitioners had blue colored walls and cabinets in their practice and used fluorescent light for shade matching. Specialists always selected the shade at patients’ eye level within 5 seconds. Conclusion: Specialists have better knowledge regarding principles of tooth shade selection procedure as compared to general dentists and house surgeons. Keywords: Shade selection, Anterior teeth, Dental practitioners